Patient and Family Caregiver's Neuroticism and Conscientiousness Personality in Relation to Quality of Life of Patient With Parkinson's Disease: A Cross-Sectional Study Neuroticism and Conscientiousness Personality in Relation to QoL of Patient With PD - Ma, Xiaoye; Meng, Guilin; Tan, Yan; Liu, Xiaohui; Zhao, Yichen; Yu, Jia; Jin, Aiping; Zhao, Yanxin; Liu, Xueyuan (Frontiers in Neurology, 2018)
Background: Personality impacts life expectancy and comprehensive treatment efficacy for patients with Parkinson's disease (PD). However, current research fails to involve the family caregiver's personality despite significant external support provided by family caregivers. This study explored neuroticism and conscientiousness personality factors of the patient and family caregiver associated with quality of life (QoL) of PD patients. Methods: 134 couples of patients presenting with PD and their family caregivers that met inclusion criteria, were recruited for this cross-sectional study at Shanghai Tenth People's Hospital from October 2015 to 2017. The Parkinson's Disease Questionnaire-39 Items (PDQ-39) for QoL, including the physical component summary (PCS) and mental component summary (MCS), the Neuroticism Extraversion Openness Five-Factor Inventory (NEO-FFI) for neuroticism and conscientiousness personalities, and the Unified Parkinson's Disease Rating Scale (UPDRS) for PD severity questionnaires were employed. Multivariate stepwise linear regression determined the contributions of demographic, clinical and personality variables in PDQ-39, PCS, and MCS. Results: PD patients and neuroticism were significantly associated with total PDQ-39, PCS, and MCS. Additionally, conscientiousness was significantly associated with PDQ-39 and PCS. After adding neuroticism and caregiver conscientiousness personality, the importance of neuroticism for the QoL model dramatically decreased, and caregiver conscientiousness personality was associated with lower scores in total PDQ-39 and PCS. Conclusion: We revealed a significant association between neuroticism and physical or mental status of PD patients; however, this association decreased when caregiver conscientiousness was added to the model. Moreover, conscientiousness of patients and caregivers were associated with improved QoL.